GAMBARAN PELAKSANAAN ISOLASI PADA PASIEN COVID-19 DI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA (BPSDM) PROVINSI JAWA BARAT (Jurnal Keperawatan Indonesia Florence Nightingale, 2022)
The increase in the number of positive cases of COVID-19 in Indonesia is one of the biggest problems we are currently facing. Various kinds of healing methods are being carried out by all health workers. The same is true for all Indonesian citizens, including preventing the spread of COVID-19. One of the transmission prevention methods recommended by the Ministry of Health is to isolate yourself, be it self-isolation at home or in isolation provider facilities. The purpose of this study was to determine the implementation of isolation in patients with COVID-19 at the Human Resources Development Agency (BPSDM) of West Java Province. This research is a descriptive quantitative research. The population in this study were patients with COVID-19 who were undergoing treatment at the West Java Province Human Resources Development Agency (BPSDM). The sample in this study were 30 patients using purposive sampling technique. Data was collected by distributing online questionnaires in the form of Google Form. The results of this study indicate that almost all patients with COVID-19 at the BPSDM of West Java Province, as many as 29 respondents (96.7%) have carried out isolation properly and correctly, which includes the implementation of the use of PPE, privacy/beds, access to open spaces, availability of clean water, hand hygiene, toilets, washing clothes, garbage, ventilation, food logistics, food equipment, access to entertainment, worship facilities, access to evacuation, and families. It can be concluded that the implementation of the isolation of patients with COVID-19 at the BPSDM of West Java Province is in the good category. It is recommended that the implementation of COVID-19 isolation at the West Java Province Human Resources Development Agency (BPSDM) can be maintained and improved to prevent more cases from occurring.